2020
DOI: 10.1111/ijfs.14468
|View full text |Cite
|
Sign up to set email alerts
|

Safe preparation of beefy meaty peptide with Bacillus subtilis

Abstract: Summary Preparation of flavour peptides with microorganisms is an attractive choice for its large‐scale production. However, beefy meaty peptide (BMP), as a research hotspot in the field of umami peptide, has been studied in few microorganisms, and furthermore, the safe preparation of BMP has not yet been reported. In this study, multi‐copy BMP (8BMP) was successfully expressed and produced in the ‘generally recognized as safe’ Bacillus subtilis (B. subtilis). Firstly, 8BMP with the potentially intense umami w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…(2010), Wu et al. (2020), and Wang et al. (2011) found umami taste after biological synthesis of the peptide.…”
Section: Umami Peptidesmentioning
confidence: 97%
See 1 more Smart Citation
“…(2010), Wu et al. (2020), and Wang et al. (2011) found umami taste after biological synthesis of the peptide.…”
Section: Umami Peptidesmentioning
confidence: 97%
“…For example, Yamasaki-isolated beef meat peptides (BMPs) were umami (Yamasaki & Maekawa, 1978). Wassenaar et al (1995) found no umami taste after the chemical synthesis of the peptide, but Zeng et al (2010), Wu et al (2020), and Wang et al (2011) found umami taste after biological synthesis of the peptide. Zhang et al (2017) analyzed several possible reasons: first, the preparation method of umami peptides may affect the analysis of peptides; second, the isomers of peptides can also affect the taste of peptides; and, third, the difference in spatial structure interferes with the analysis of umami taste.…”
Section: Structure-activity Relationship Of Umami Peptidesmentioning
confidence: 99%
“…For example, multicopy BMP in Bacillus subtilis was successfully expressed through the target gene tandem strategy. 5 A food-safe B. subtilis expression system was obtained and the high-density fermentation process of BMP was explored, which eventually improved the yield of BMP. 6 However, the drawback of these approaches is that the recombinant expression of short-chain peptides is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, researchers have tried to express BMP in engineered bacteria by genetic engineering to obtain this peptide in large quantities. For example, multicopy BMP in Bacillus subtilis was successfully expressed through the target gene tandem strategy . A food-safe B.…”
Section: Introductionmentioning
confidence: 99%